Evaluation of the Bond Strength of Resin Cements Used to Lute Ceramics on Laser-Etched Dentin - EREN GİRAY, FİGEN (MARY ANN LIEBERT, INC, 2014)
Objective: The purpose of this study was to investigate the shear bond strength (SBS) of two different adhesive resin cements used to lute ceramics on laser-etched dentin. Background data: Erbium, chromium: yttrium, scandium, gallium, garnet (Er, Cr: YSGG) laser irradiation has been claimed to improve the adhesive properties of dentin, but results to date have been controversial, and its compatibility with existing adhesive resin cements has not been conclusively determined. Materials and methods: Two adhesive cements, one etch-and-rinse [Variolink II (V)] and one self-etch [Clearfil Esthetic Cement (C)] luting cement, were used to lute ceramic blocks (Vita Celay Blanks, Vita) onto dentin surfaces. In total, 80 dentin specimens were distributed randomly into eight experimental groups according to the dentin surface-etching technique used Er, Cr: YSGG laser and Er: YAG laser: (1) 37% orthophosphoric acid + V (control group), (2) Er, Cr: YSGG laser + V, (3) Er, Cr: YSGG laser + acid + V, (4) Er: YAG laser + V, (5) Er: YAG laser + acid + V, (6) C, (7) Er, Cr: YSGG laser + C, and (8) Er: YAG laser + C. Following these applications, the ceramic discs were bonded to prepared surfaces and were shear loaded in a universal testing machine until fracture. SBS was recorded for each group in MPa. Shear test values were evaluated statistically using the Mann-Whitney U test. Results: No statistically significant differences were evident between the control group and the other groups (p > 0.05). The Er, Cr: YSGG laser + A + V group demonstrated significantly higher SBS than did the Er, Cr: YSGG laser + V group (p = 0.034). The Er,Cr: YSGG laser + C and Er: YAG laser + C groups demonstrated significantly lower SBS than did the C group (p < 0.05). Conclusions: Dentin surfaces prepared with lasers may provide comparable ceramic bond strengths, depending upon the adhesive cement used.
Keywords: ER-YAG-LASER; ER,CRYSGG LASER; PREPARED DENTIN; SHEAR-STRENGTH; MICRO-TENSILE; GARNET LASER; COMPOSITE; ENAMEL; SURFACES; ADHESION